D-modules in complex dimension 1 (2019)
"The work begins by exposing the basic theory of systems of complex differential equations, followed by a study of systems with one regular singularity. The equivalence between systems with a regular singularity and representations of the fundamental group is proven. The work finalizes with an introduction to the D-module perspective for studying the problem."--Tomado del Formato de Documento de Grado.